Begränsad tillväxt av fjällbjörkplantor över årtionden har liten inverkan på den omgivande tundran - Scharn, Ruud; Negri, Isabel S.; Løkken, Jørn O.; Bacon, Christine D.; Antonelli, Alexandre; Hofgaard, Annika; Nilsson, R. Henrik; Björk, Robert (Swedish National Data Service, 2022)
The study addresses two important issues in arctic treeline dynamics: • How do birch saplings, being the dominant treeline species, that have been established above treeline perform? • How do these birch saplings affect the surrounding tundra vegetation? For this, we collected species abundance measurements in 50 x 50 cm plots around birch saplings above the treeline near the Latnjajaure Field Station in northern Sweden. We compared these measurements with control measurements, and reference measurements taken below the treeline. We also looked at the growth (Diameter + Length) of birch saplings over 15 years (2001-2016). The data deposited includes the raw data, code, and statistical models used to analyze the data, and all output (figures and tables) used in the study. Further metadata can be found in the README file included with the data. GENERAL INFORMATION 1. Title of Dataset: Limited decadal growth of mountain birch saplings has minor impact on surrounding tundra vegetation 2. Author Information A. Principal Investigator Contact Information Name: Ruud Scharn Institution: University of Gothenburg Email: ruud.scharn@gu.se B. Associate or Co-investigator Contact Information Name: Robert Björk Institution: University of Gothenburg Email: robert.bjork@gu.se 3. Date of data collection: 2016-07-(4-31) 4. Geographic location of data collection Latnjajaure field station close to Abisko northern Sweden (68.35°N, 18.49°E). DATA & FILE OVERVIEW The file birch_coordinates.csv contains the coordinates of each birch (WGS84 and SWEREF99) together with height, number of stems, base diameter and number of branches. For each analysis in the paper, we created a folder containing three subfolders The main folders: 1 alpha diversity altitude slope 2 alpha diversity intercept only 3 Beta diversity 4 Diameter and length Subfolders are structured the same for all main folders containing: 1 input: containing raw input data. 2 script: R Script containing all data processing as well as the JAGS script containing the code used in ...